An Empirical Analysis of Accounting Students’ Career Plans in Kazakhstan (Journal of Economic Research & Business Administration, 2018)
This study determines the factors influencing accounting students’ choices to pursue their career asa chartered accountant or not. A survey method is used to collect the data. 200 students from 5 differentuniversities from Almaty region participated in this study. Exploratory Factor Analysis (EFA) findingsreveal 5 different factors such as; (i) power, (ii) fringe benefits, (iii) soft skills, (iv) personal developmentas well as (v) physical and emotional safety. Further, it was found that accounting students in Kazakhstanwho intend to choose a career in accounting give a much higher priority to their soft skills and financialfactors in the form of fringe benefits than those who have chosen other career. The results of this studymight have some practical implications as they might open new perspectives for restructuring accountingcurriculum. Other implications of this study may help students in the accounting field to understand theirabilities and skills, as well as help them better navigate in their future career. Theoretical implications andlimitations are discussed.